Efforts to Form the Religious Character of Students Through Islamic Spiritual Extracurricular Activities at Junior High School in Surabaya - Nabillah, Sayyid Qutub; Eli Masnawati; Amir Bandar Abdul Majid (International Journal of Islamic Thought and Humanities, 2024)
This study aims to explore and describe various efforts made to shape the religious character of students through the extracurricular activities of Islamic Spirituality (Rohis) Pro Patria at YP 17 High School Surabaya. The main problem in this study is how Rohis's activities function as an effective medium in developing the religious character of students, amidst the moral challenges of today's young generation. This study applies a qualitative approach with a case study design. The data collection process was carried out through observation techniques, in-depth interviews with Rohis instructors, Islamic Religious Education teachers, and active Rohis members, and documentation of activities. The results of the study showed that Rohis extracurricular activities at  YP 17 High School Surabaya were carried out in a structured manner through routine programs such as Islamic studies (Hadith Arbain, Tauhid, Fikih, and Muhadharah), Reading and Writing the Qur'an (BTQ), Islamic arts (Sholawat Quraniyah and Al-Banjari), and the habituation of daily worship such as the call to prayer and congregational prayer. These programs play an active role in instilling religious values, forming positive habits, and increasing students' spiritual awareness. The implication of this finding is the importance of supporting and developing religious-based extracurricular programs as part of the character education strategy in schools.